Do Not Conform to the Patterns of this World! A Postcolonial Investigation of Performativity, Metamorphoses and Bodily Materiality in Romans 12. (September 2014) - Auga, Ulrike; Schirr, Bertram J.
The coexistence of radically resistant body theology and unrestricted demands for submission in Rom. 12 and 13 presents a unique and unsettling dilemma for feminist and postcolonial exegetes and theorists. With a critical discussion of postcolonial hybridity theory and a turn towards – and back to – performativity this paper pushes the deviant metaphoricity in Rom. 12 from a shadowy existence to the centre stage and thereby redevelops Pauline concepts of perpetual bodily transformations as a challenge to reified body ideologies. We demonstrate how the marginalized, subjugated and colonized body experience of St. Paul becomes a resource for opening, materialized and pervasive stimuli that go beyond essentializing identitarian and excluding body configurations.